Non-ideal victims or offenders?: the curious case of pyramid scheme participants - Hock, Branislav (Scams, cons, frauds, and deceptions, 2024)
Pyramid schemes, including their various forms such as chain letters and illegal forms of multi-level marketing, harm people that are often far from ideal victims. While many lose cash and suffer emotional, health, and other harms; victims also facilitate pyramids by actively recruiting new victims and turning them into more recruiters ad nauseam. Research in this area is, however, small. This paper seeks to add to this small body of research by constructing a typology of actors in pyramid schemes being inspired by concepts of ideal victim and non-ideal victim and building upon the characteristics of pyramid schemes. It provides a unique insight into a complex network of relationships featured by pyramid schemes and contentious areas between victims and perpetrators of economically motivated crimes and wrongs. The paper presents policy implications and argues more research is needed on this group and their needs as they are often neglected by the criminal justice systems.